Neoliberal gremlins? How a scheme to help disadvantaged young people thrive online fell short of its ambitions - Davies, H; Eynon, R; Wilkin, S (Routledge, 2017)
Numerous academic studies highlight the significant differences in the ways that young people access, use and engage with the Internet and the implications it has in their lives. Trying to address such inequalities is complex, and the outcomes of digital inclusion schemes are rarely uniformly positive or transformative for the people involved. Therefore the hope of such schemes that if sufficiently empowered, incentivised and aspirational, the disadvantaged can use access to technology to transform or transcend what Bourdieu [1992. The logic of practice. Studies in philosophy and education. Cambridge: Polity Press; New Ed edition] calls their ‘class of conditions’ (p. 53) is largely misplaced. This gap between expectation and reality demands theoretical attention. Focusing on a two-year digital inclusion scheme for 30 teenagers and their families in one area of England, this qualitative study analyses why, despite the good intentions of the scheme’s stakeholders, it fell short of its ambitions. Instead, our theoretical analysis explains how the neoliberalist systems of governance that are increasingly shaping the cultures and behaviours of our Internet service providers and schools cannot solve the problems they create.